Condition of Seagrass Beds Ecosystem on Poncan Gadang Island Based on Macrozoobenthos Diversity - Elpiyani Elpiyani; Ruri Rimenta Ximenez Diaz; Nuratika Ranza; Diana Khairiyah Sirait; Rusdi Machrizal (Jurnal Penelitian Pendidikan IPA, 2023)
The seagrass ecosystem of Poncan Gadang island is one of the ecosystems that often come under pressure due to ecotourism activities. Pressure on these ecosystems can have an impact on the diversity of the types of animals that live in them. This research is aimed at knowing the condition of seagrass ecosystems based on the diversity of macrozoobenthos that live in them. The observation point is divided into 5 stations. At each point, a square transect of 1x1 meters is made as many as 10 pieces. Collection of macrozoobenthos samples is carried out by the hand sorting method. The samples collected were then identified at the Ecology Laboratory of the Faculty of Teacher Training and Education, University of Labuhanbatu. Data analysis uses the shannon wienner index (H'), Dominance Index (C') and Similarity Index (IS) formulas. Data analysis was done by computer program Plymouth Routines In Multivariate Ecological Research (Primer) 7th version. The results showed that there were 30 species of macrozobenthos living in the seagrass ecosystem of Poncan Gadang island, with a diversity index (H') of 3.031-3.191, a dominance index (C') of 0.0038 - 0.0053, then a similarity index (IS) of 86.792 – 98.305%. This result indicates the condition of the seagrass beds ecosystem of Poncan Gadang Island is in good condition, with a moderate level of uniformity, low dominance and high similarity